On the nature and direction of relationships between constructs and measures - Edwards, J R; Bagozzi, R P (Psychological methods, 2000)
Theory development typically focuses on relationships among theoretical constructs, placing little emphasis on relationships between constructs and measures. In most cases, constructs are treated as causes of their measures. However, this causal flow is sometimes reversed, such that measures are viewed as causes of constructs. Procedures have been developed to identify and estimate models that specify constructs as causes or effects of measures. However, these procedures provide little guidance for determining a priori whether constructs should be specified as causes or effects of their measures. Moreover, these procedures address few of the possible causal structures by which constructs and measures may be related. This article develops principles for specifying the direction and structure of relationships between constructs and measures. These principles are illustrated using examples from psychological, sociological, and organizational research.